Relevansi Kepemimpinan Hindu Dalam Organisasi di Era Milenium - I Made Suasti Puja; I Gede Aryana Mahayasa (Widya Manajemen, 2021)
The purpose of this research is to know and understand the relevance of Hindu leadership in the millennial era so that the millennial generation has the desire to study and deepen Hindu leadership so that it is implemented in managing an organization that can be aligned with advances in science and technology. The research method used in this study uses a library research method or approach. Literature study or literature can be interpreted as a series of activities related to methods of collecting library data, reading and taking notes and processing research materials. The conclusion is that the concept of Hindu leadership is still relevant to be applied in the current millennium, such as the leadership of Kautilya, Asta Brata, Krishna and Tri Hita Karana because it is universal and laden with moral values ​​so that it can become a leadership model in the future.